Methodological Issues in Internet-Mediated Research: A Randomized Comparison of Internet Versus Mailed Questionnaires - Whitehead, Lisa (Gunther Eysenbach, 2011)
BACKGROUND: The majority of Internet-mediated studies use measures developed as paper-and-pencil measures or face-to-face-delivered material. Previous research suggests that the equivalence between online and offline measures must be demonstrated rather than assumed. OBJECTIVE: The objective of this study was to explore the equivalence 4 measures completed in an online or offline setting. METHODS: A sample of students (n = 1969) was randomly assigned to complete 4 popular scales (the SF-12v2, the Hospital Anxiety and Depression Scale (HADS), the Fatigue Symptom Inventory, and a single-item fatigue measure) either online or by mail survey (pencil and paper). The response rate was 52.51% (n = 1034) and comparable between the online and offline groups. RESULTS: Significant differences were noted in fatigue levels between the online and offline group (P = .01) as measured by the Fatigue Symptom Inventory, with the online sample demonstrating higher levels of fatigue. Equivalency was noted for the SF-12v2, the Hospital Anxiety and Depression Scale, and the single-item fatigue measure. Internal consistency was high except for the SF-12v2. The SF-12v2 may not be an ideal measure to use for remote administration. CONCLUSIONS: Equivalency of the Hospital Anxiety and Depression Scale (HADS) and the Physical Component Score and Mental Component Score of the SF-12v2 for online and offline data were demonstrated. Equivalency was not demonstrated for the Fatigue Symptom Inventory. Explanations for the difference in fatigue score between the online and offline samples are unclear. Research that seeks to match samples and control for extraneous online and offline variables is called for, along with exploration of factors that may mediate the completion of questionnaires or alter the respondents’ relationship with the same, to enhance progress in this area.